Significance of Platelet Indices Other Than Thrombocytopenia as Severity Marker in Preeclamptic Cases Attending Al-Elwiyah Maternity Teaching Hospital - Amash, Aya Amer; Al-Haidari, Taghreed Khalil (Journal of Science in Medicine and Life, 2026)
Background: Preeclampsia is a serious pregnancy complication, affecting 2-8% of pregnancies worldwide, characterized by elevated blood pressure, and proteinuria. It poses significant maternal and fetal health risks, necessitating better diagnostics and prognostics tools. Platelets play a complex role in preeclampsia, and their indices may offer insights into the condition's severity and progression, aiding in early detection and treatment guidance. Aim of the study: This study evaluates platelet indices (MPV, PDW, PCT) in non-thrombocytopenic preeclampsia cases at Al-Elwiyah Maternity Teaching Hospital to gauge preeclampsia severity. Patients and methods: This cross-sectional study was conducted at Al-Elwiya Maternity Teaching Hospital from January 2023 to December 2023, involving 300 women (150 with preeclampsia, 150 healthy pregnant as controls). detailed data collected through questionnaires, physical examinations, and laboratory analyses of platelet indices (MPV, PLT, PCT, PDW). The cases were compared according to the rate of complications and predictive ability of platelet indices. Results: The maternal age, gestational age, and parity did not significantly differ between groups. Liver enzymes were markedly elevated in severe cases. Platelet count and PCT were lower in severe preeclampsia, while platelet indices (MPV, PDW) were higher. ROC analysis demonstrated excellent discriminative ability for MPV (AUC=0.95), PDW (AUC=0.926), and PCT (AUC=0.945) in predicting severe preeclampsia, with (MPV: Sensitivity 81.3%, Specificity 85.8%; PDW: Sensitivity 92%, Specificity 86.7%; PCT: Sensitivity 70.7%, Specificity 94.7%). Conclusion: Platelet indices, particularly MPV and PDW, correlate strongly with preeclampsia severity. MPV and PDW are valuable for severe cases, while PCT is more specific but less sensitive. These indices can aid in early preeclampsia severity assessment and management.